Review of financial capability studies - Zakaria, Nurul Farhana; Sabri, Mohamad Fazli (Center for Promoting Ideas, 2013)
Financial capability or the ability of people to manage their day-to-day finances is receiving an increasing interest among policy makers and researchers as more people find themselves in difficult financial situations especially during the economic downturn. Alarmed by this situation, the purpose of this paper is to tackle the problem of how to measure financial capability with a specific focus on general four domains; managing money, staying informed, choosing products and planning ahead. The study concludes with financial capability studies in ten countries which provide the similarities and differences in measuring financial capability. From the evidence reviews, it finds the lowest financial capability is among the young people who is under 45 years old, women, married or living with a partner, those on low income and low levels of education, literacy and numeracy. In contrast, older men and women who live with employed spouse have the most financial capability.